Comparative Genomics Reveals a Single Nucleotide Deletion in pksP That Results in White-Spore Phenotype in Natural Variants of Aspergillus fumigatus - Gibbons, John G.; D’Avino, Paolo; Zhao, Shu; Cox, Grace W.; Rinker, David C.; Fortwendel, Jarrod R.; Latge, Jean-Paul (Frontiers in Fungal Biology, 2022)
Aspergillus fumigatus is a potentially deadly opportunistic human pathogen. A. fumigatus has evolved a variety of mechanisms to evade detection by the immune system. For example, the conidium surface is covered in a layer of 1,8-dihydroxynaphthalene (DHN) melanin which masks the antigen macrophages use for recognition. DHN melanin also protects conidia from ultraviolet radiation and gives A. fumigatus conidia their characteristic green-grayish color. Here, we conducted genomic analysis of two closely related white-spore natural variants of A. fumigatus in comparison to two closely related green-spore isolates to identify a genetic basis of the white-spore phenotype. Illumina whole-genome resequencing data of the four isolates was used to identify variants that were shared in the white-spore isolates and different from both the green-spore isolates and the Af293 reference genome (which is also a green-spore isolate). We identified 4,279 single nucleotide variants and 1,785 insertion/deletions fitting this pattern. Among these, we identified 64 variants predicted to be high impact, loss-of-function mutations. One of these variants is a single nucleotide deletion that results in a frameshift in pksP (Afu2g17600), the core biosynthetic gene in the DHN melanin encoding gene cluster. The frameshift mutation in the white-spore isolates leads to a truncated protein in which a phosphopantetheine attachment site (PP-binding domain) is interrupted and an additional PP-binding domain and a thioesterase domain are omitted. Growth rate analysis of white-spore and green-spore isolates at 37°C and 48°C revealed that white-spore isolates are thermosensitive. Growth rate of A. fumigatus Af293 and a pksP null mutant in the Af293 background suggests pksP is not directly involved in the thermosensitivity phenotype. Further, our study identified a mutation in a gene (Afu4g04740) associated with thermal sensitivity in yeasts which could also be responsible for the thermosensitivity of the white-spore mutants. Overall, we used comparative genomics to identify the mutation and protein alterations responsible for the white-spore phenotype of environmental isolates of A. fumigatus.